Time‐Lapsed Hydraulic Tomography for Monitoring Hydraulic Conductivity Field Evolution Caused by Pore‐Clogging - Bing‐Shiun Ke; Yo‐Jin Shiau; Bo‐Tsen Wang; Chia‐Hao Chang; Tian‐Chyi Jim Yeh; Jui‐Pin Tsai (Water Resources Research)
Abstract In situ chemical oxidation (ISCO) is widely used for soil and groundwater remediation. However, reagents often cause pore clogging due to metal ion precipitation, reducing hydraulic conductivity (K) and altering flow paths. This study investigates the impact of pore‐clogging on three‐dimensional K and flow fields during Fenton's reagent injection in a sandbox experiment. Time‐lapsed, steady‐state hydraulic tomography (HT) was employed to quantify the spatial evolution of the K field. Soil cores from low‐K regions were analyzed using inductively coupled plasma‐optical emission spectrometry for total iron (TI) concentration. Experimental results reveal a negative correlation between K and TI, with a maximum 56.5% decrease in K corresponding to a 30.8% increase in TI. This finding supports the use of HT to monitor K evolution due to pore clogging. We also found that pore‐clogging primarily occurred in high‐K zones near injection points. Solute transport simulation results based on the original and pore‐clogged K fields indicate that pore‐clogging impedes reagent transport, as evidenced by a larger high‐concentration region in the original K field. These results demonstrate that pore‐clogging from Fenton's reagent injection significantly affects K and reagent transport. Therefore, time‐lapsed HT is essential for updating K and flow fields to optimize reagent injection strategies. These findings provide valuable insights for hydraulic–geochemical studies, particularly in contaminated site remediation.